A rare case of cervical dysgenesis presented with endometriosis and ectopic kidney - Gupta, Shivani; Yadav, Garima; Singh, Pratibha; Shekhar, Shashank (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Cervical dysgenesis is a rare cause of obstructive amenorrhoea. We are presenting a case of a 15-year-old girl presented with primary amenorrhoea diagnosed with cervical dysgenesis with left ectopic kidney and endometriosis. The patient underwent laparoscopy followed by exploratory laparotomy with total abdominal hysterectomy with left salpingectomy followed by neovaginal creation and right ureteric D-J stenting and vaginal mould insertion. Cervical agenesis treatment should aim at the re-establishment of patency of the outflow tract. A fistulous tract with stent placement has been done in some cases but eventually, hysterectomy is required in view of recurrent and severe pelvic infection is a common problem. Ovarian function can be preserved if a hysterectomy is performed timely.